Medal shares in Winter Olympic Games by sport: Socioeconomic analysis after Vancouver 2010 - Otamendi, F. J.; Doncel, L. M. (Social Science Quarterly, 2014)
Objectives: The quantitative analysis of the medal shares (MSs) in recent Winter Olympic history by sport and country will identify the relevant socioeconomic factors that are likely to derive policy issues. Methods: Econometric modeling and concentration indices are used to predict and assess MSs by sport and country. The development of a mathematical routine to convert MSs to counts and the proposal of a modified Herfindahl index has added robustness to the analysis. Results: The deviations of the predictions for Vancouver (2010) <http://www.vancouver2010.com/> from the observed values pinpoint significant factor differences among the sports. Medal concentrations are different by sport in the number of countries and their names. Conclusions: Tradition and geography are primary factors affecting the medal-winning process. Concerning feasible policies for newcomers, nationalization of athletes, development of talent identification systems, and fostering the participation in sports without a "monopolistic" winner could become short - and long-run successful paths.